Estudo comparativo do uso do clipe de titânio no tratamento do coto apendicular durante apendicectomia laparoscópica em 533 casos utilizando o Escore de Gomes - Cleber Soares Junior (2015)
Background: the closure of the appendiceal stump during appendectomy has been performed in different ways; however, the use of titanium metal endoclip has not been evaluated yet in a prospective way. Purpose: to analyse the results of applying metal endoclip in the treatment of the appendiceal stump among its different grades according Gomes et al. score and between complicated and non complicated grades of appendicitis. Method: in between January 2005 and January 2014, 533 patients had been underwent laparoscopic appendectomy for acute appendicitis. All patients were graded according Gomes et al. classification: 0,1, 2, 3A, 3B, 4A, 4B, 5 grades. There have been evaluated 533 consecutive patients who had been underwent to a laparoscopic appendectomy using metal endoclipping for appendiceal stump closure. Among them, 222 patients had non complicated forms (grades 1 and 2), and 270 patients had complicated forms (grades 3A, 3B, 4A, 4B and 5) of acute appendicitis; Forty-one patients did shown appendicitis in postoperative histological examination (grade 0). The age ranged varied from 12 to 75 years old (31.1± 12.3 years old) and 51.6% were male. Tests for statistical significance included the Chi-square and Fisher’s exact tests for intergroup differences concerning its viability, reliability, intraoperative complications and surgical site infections. A power analysis was performed to determine the minimum sample size of both patient groups needed to achieve (1- β)=0.80 power with a probability value of α=0.05; this analysis suggested the sample size should be a minimum of 26 patients in each group. Results: the appendiceal stump closure by metal endoclip was effective in 495 patients (92.9%). The comparative analysis of non complicated and complicated forms has shown viability in 95.9% and 89.2% respectively (p=0.006). The appendix base necrosis (grade 3B) was the main constraint to the method, considering that in that group just in 48.2% of the patients it was possible to make use of the endoclip (p≤0.001) when compared with the other clinical forms). The comparative analysis of viability between non complicated and complicated forms after excluding patients with base necrosis (grade 3B) did not shown diference (p=0.302). Infection of superficial surgical site and intraperitoneal infection had happened in 12 cases (2.4%) and 11 cases (2.2%) respectively. However, 91.6% of superficial surgical site infection and 90.9% of peritoneal cavity infection belonged to the group of acute appendicitis complicated forms (p<0.05). Superficial surgical site infection was more frequent in grade grade 3B when compared with other grades (excluding grade 5), and also in grade 5 when compared with grade 1. Superficial surgical site infection was less frequent in grade 0 when compared with other grades (excluding grade 0). There have been more intra-abdominal abscess when grade 3B was compared with grades 1, 2 and 3A; and in grades 4A and 5 when compared with grade 2. Conclusion: the appendiceal stump closure by metal endoclip has proved to be a safe and effective procedure. The presence of appendix base necrosis has been the bigger constraint of the method. The frequency of infectious complications was higher in grades 3B (base necrosis), 4A (abscess) and 5 (difuse peritonitis); and higher in complicated forms of acute appendicitis than uncomplicated ones (p<0.05), but without relationship to the clip application.